Long Non-coding RNA CDKN2B Antisense RNA 1 Gene Contributes to Paclitaxel Resistance in Endometrial Carcinoma - Shang, Chao; Ao, Cheng N.; Cheong, Chi C.; Meng, Lirong (Frontiers in Oncology, 2019)
Endometrial cancer (EC) is the most common malignancy of the female reproductive tract. In this study, we clarified the clinical significance of CDKN2B antisense RNA 1 (CDKN2B-AS) gene, and its effects on paclitaxel sensitivity in EC. Firstly, CDKN2B-AS gene was highly expressed in EC tissues and cell lines. The high-expression of CDKN2B-AS gene was associated with high pathological grade and low paclitaxel sensitivity of EC tissues. Knockdown of CDKN2B-AS gene sensitized Ishikawa/PA and HEC1A/PA cells to paclitaxel, and promoted paclitaxel-induced cytotoxicity. Secondly, the low-expression of miR-125a-5p was closely associated with low paclitaxel sensitivity of EC cells, and up-regulation of miR-125a-5p could increase paclitaxel sensitivity of Ishikawa/PA and HEC1A/PA cells. MiR-125a-5p also mediated the suppressive effects of knockdown of CDKN2B-AS on paclitaxel resistance in EC cells. Thirdly, B-cell lymphoma-2 (Bcl2) and Multidrug Resistance-Associated Protein 4 (MRP4) genes were target genes of miR-125a-5p, which modulated paclitaxel resistance of Ishikawa/PA and HEC1A/PA cells through targeted silencing Bcl2 and MRP4. In conclusion, high-expression of CDKN2B-AS is associated with a poor response to paclitaxel of EC patients, and knockdown of CDKN2B-AS inhibits paclitaxel resistance through miR-125a-5p-Bcl2/MRP4 pathway in EC patients. Our findings help elucidate the molecular mechanisms of chemoresistance in EC patients.